Long-segment common carotid occlusion presenting with limb-shaking transient ischemic attack: Case report - Jiang, Qingjun; Bai, Jun; Nie, Shaojie; Jin, Jie; Qu, Lefeng (Frontiers in Surgery, 2023)
BACKGROUND: Limb-shaking transient ischemic attack (LS-TIA) is a rare manifestation of carotid artery occlusion. Common carotid artery occlusion (CCAO) is a relatively rare condition, and both its natural history and recommendations for treatment are still unclear. CASE DESCRIPTION: A 67-year-old female suffered from transient episodes of unilateral limb shaking. Computer tomographic angiography (CTA) showed long-segment occlusion of the right common carotid artery. Computer tomographic perfusion (CTP) demonstrated hypoperfusion of the corpus striatum, which suggests that hemodynamic failure is a potential mechanism underlying the LS-TIA secondary to common carotid artery occlusion. The occlusion was successfully recanalized by retrograde common carotid endarterectomy, and the episodes of left limb shaking disappeared after surgery. CONCLUSIONS: The occlusion was successfully recanalized by retrograde common carotid endarterectomy, and the episodes of left limb shaking disappeared after surgery. Hypoperfusion of the corpus striatum might be a potential mechanism underlying the LS-TIA secondary to common carotid occlusion.